2004
DOI: 10.1021/jf035214p
|View full text |Cite
|
Sign up to set email alerts
|

Specific Synthesis of 5,5‘-Dicapsaicin by Cell Suspension Cultures of Capsicum annuum Var. annuum (Chili Jalapeño Chigol) and Their Soluble and NaCl-Extracted Cell Wall Protein Fractions

Abstract: HPLC-UV, (1)H NMR, (13)C NMR, and (1)H-(1)H COSY analyses revealed that exogenous capsaicin was specifically converted into 5,5'-dicapsaicin by both cell suspension cultures of Capsicum annuum var. annuum (chili Jalapeño chigol) and their soluble and NaCl-extracted cell wall protein fractions under oxidative conditions. In cell suspension cultures 5,5'-dicapsaicin was found only in biomass of capsaicin-fed cultures. This compound has not been detected before either in fresh fruits or in in vitro cultures of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…There are many authors that had found capsaicin in other plant tissues, e.g., in cellular suspensions (Martínez-Juarez et al, 2004;Ravishankar, 2002, 2003), but in our laboratory, under our conditions, we never had found capsaicinoids in noninductive conditions in cell suspensions of habanero pepper (data not shown).…”
Section: Determination Of Capsaicinoids In Leaves and Stems Of Habanecontrasting
confidence: 44%
“…There are many authors that had found capsaicin in other plant tissues, e.g., in cellular suspensions (Martínez-Juarez et al, 2004;Ravishankar, 2002, 2003), but in our laboratory, under our conditions, we never had found capsaicinoids in noninductive conditions in cell suspensions of habanero pepper (data not shown).…”
Section: Determination Of Capsaicinoids In Leaves and Stems Of Habanecontrasting
confidence: 44%
“…No further damage to these structures was recorded throughout the culture period, neither the formation of new ones (Figures 2(b) and 2(c) ). Nevertheless, CAPs recovered from the medium were in very low concentrations, perhaps due to their oxidation, as has been previously proposed [ 18 ]. This fact may explain the cause of lower CAPs contents in immobilized placentas when compared to the intact tissue excised from pepper pods ( ca .…”
Section: Resultsmentioning
confidence: 62%
“…e HPLC/UV analysis of the phenolic profile was performed with acetonitrile and trifluoroacetic acid (TFA) as the mobile phase as reported by Martínez-Juarez et al [25], using an HPLC system with a 20 µL loop and a Spectra System UV-visible optical scanning detector ( ermo Separation Products Inc.) that allows the UV/VIS detection of all solutes eluting from the HPLC column. e detector signals were captured and processed by the PC1000 system software ( ermo Separation Products Inc.).…”
Section: Hplc/uv Analysismentioning
confidence: 99%